2020
DOI: 10.20944/preprints202008.0570.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

White Mold on Pea Caused by <em>Sclerotinia sclerotiorum</em>: A New Threat for Pea Cultivation in Bangladesh

Abstract: A new disease causing the tan to light brown blighted stems and pods has occurred in 2.6% pea (Pisum sativum L.) plants with an average disease severity rating of 3.7 in Chapainawabganj district, Bangladesh. A fungus with white appressed mycelia and large sclerotia was consistently isolated from symptomatic tissues. The fungus formed funnel-shaped apothecia with sac-like ascus and endogenously formed ascospores. Healthy pea plants inoculated with the fungus produced typical white mold symptoms. The internal tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Nahar et al, 2020 reported up to 100% White mold infection at the surveyed field in the northwest region of Bangladesh. White mold (Sclerotinia sclerotiorum) of pea has recently emerged as a new threat to pea production in Bangladesh (Islam et al, 2020). In Bangladesh, Sclerotinia sclerotiorum was also reported for the first time to cause stem and pod blight of common bean (Prova, et al, 2014) 2002).…”
Section: Diseases Of Beanmentioning
confidence: 99%
“…Nahar et al, 2020 reported up to 100% White mold infection at the surveyed field in the northwest region of Bangladesh. White mold (Sclerotinia sclerotiorum) of pea has recently emerged as a new threat to pea production in Bangladesh (Islam et al, 2020). In Bangladesh, Sclerotinia sclerotiorum was also reported for the first time to cause stem and pod blight of common bean (Prova, et al, 2014) 2002).…”
Section: Diseases Of Beanmentioning
confidence: 99%